Relationship of pregnant mother’s anxiety level with preparation for childbirth during Covid-19 pandemic in Surabaya, Indonesia - Irma Maya Puspita; Nova Elok Mardliyana (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHT1. Due to Covid-19 pandemics, anxiety among pregnant mothers is increasing and good preparation for childbirth is needed.2. A survey was carried out to find pregnant mothers level of anxiety and preparation for childbirth during the pandemics.3. Most of the pregnant mothers were severely anxious, but most of them also felt prepared for childbirth. No relationship was found between anxiety and preparedness for childbirth. ABSTRACTObjective: Corona Virus (Covid-19) currently occurring in Indonesia greatly affects the health of the entire community, both physically and psychologically. During the pandemic period, social restrictions are required in an effort to reduce the spread of the virus, especially for pregnant women who are vulnerable to infection because of their weak immune system. This causes increased maternal anxiety during pregnancy. Therefore, good preparation for childbirth is needed so that mothers receive sufficient information and receive safe services from exposure to viruses.Materials and Methods: This research used an analytic survey method with cross-sectional approach by distributing closed questions on online questionnaires to pregnant women in Surabaya, Indonesia, through social media networks. The sampling technique used simple random sampling and managed to collect a sample of 90 persons.Results: This research showed that pregnant women during the Covid-19 pandemic in Surabaya, Indonesia, experienced 13% mild anxiety, 24% moderate anxiety, and 63% severe anxiety. In regard with preparation for childbirth during the Covid-19 pandemic in Surabaya, 20% were unprepared and 80% ready.Conclusion: There is no relationship between the anxiety experienced by pregnant women during the Covid-19 pandemic and their preparation for delivery. Pregnant women were worried that they can be exposed to the virus. Therefore, they can prepare for childbirth properly so that they can go through delivery safely and comfortably.